2011
DOI: 10.1021/nn2013707
|View full text |Cite
|
Sign up to set email alerts
|

Traceable Multifunctional Micellar Nanocarriers for Cancer-Targeted Co-delivery of MDR-1 siRNA and Doxorubicin

Abstract: In this article we report on the development of polymeric micelles that can integrate multiple functions in one system, including the capability to accommodate a combination of therapeutic entities with different physicochemical properties (i.e., siRNA and doxorubicin; DOX), passive and active cancer targeting, cell membrane translocation, and pH-triggered drug release. A micellar system was constructed from degradable poly(ethylene oxide)-block-poly(ε-caprolactone) (PEO-b-PCL) block copolymers with functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
294
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 390 publications
(300 citation statements)
references
References 34 publications
6
294
0
Order By: Relevance
“…Some polymers, such as -cyclodextrin, PEO-block-poly (-caprolactone) (PCL) and dextran, which do not contain amino groups in their chemical structures, can also deliver siRNA after appropriate modification [88][89][90][91][92]. Li et al [88] developed a MDR1 siRNA and Dox co-delivery system, in which CdSe/ZnSe quantum dots were coated with -cyclodextrin via amino acids L-Arg or L-His.…”
Section: Other Nanocarriersmentioning
confidence: 99%
See 2 more Smart Citations
“…Some polymers, such as -cyclodextrin, PEO-block-poly (-caprolactone) (PCL) and dextran, which do not contain amino groups in their chemical structures, can also deliver siRNA after appropriate modification [88][89][90][91][92]. Li et al [88] developed a MDR1 siRNA and Dox co-delivery system, in which CdSe/ZnSe quantum dots were coated with -cyclodextrin via amino acids L-Arg or L-His.…”
Section: Other Nanocarriersmentioning
confidence: 99%
“…With the help of -carboxyl groups, one can endow the PCL polymer with more functionality, including the abilities to deliver nuclear acid drug. Xiong et al [89,90] modified PEO-PCCL with spermine or N,Ndimethyldipropylenetriamine. Amino groups introduced in its structures bound siRNA stably via electrostatic attraction under physiological conditions.…”
Section: Other Nanocarriersmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been demonstrated that combining a chemotherapeutic agent with siRNA in a co-delivery nanocarrier can significantly enhance therapeutic efficacy. [20][21][22][23] In the past few decades, many efforts have been made to improve the solubility, stability, and pharmacokinetics of small molecule organic drugs with the aid of cyclodextrins (CDs) and their derivatives. The hydrophobic internal cavity of CDs endows them with the capability to form inclusion complexes with organic drugs, and their hydrophilic exterior (due to the presence of hydroxyl radicals) guarantees good water solubility of the complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, polymeric prodrugs can overcome inherent drawbacks of drug such as poor water solubility, chemical instability, and rapid metabolism. There are many routes for preparation of polymeric prodrugs which showed high drug loading efficiency [19,20]. They can be prepared by preformed polymers [21,22], polymerization reaction of drug-bearing monomers [23][24][25], or ring-opening polymerization of a druginitiator [26,27].…”
mentioning
confidence: 99%